Detection of Campylobacter jejuni diversity by clustered regularly interspaced short palindromic repeats (CRISPR) from an animal farm. Issue 6 (12th September 2021) - Yeh, Hung‐Yueh; Awad, Amal; Rothrock, Michael J.
Abstract: Background: Campylobacter jejuni is the leading bacterial pathogen that causes foodborne illness worldwide. Because of genetic diversity and sophisticated growth requirements of C. jejuni, several genotyping methods have been investigated to classify this bacterium during the outbreaks. One of such method is to use clustered regularly interspaced short palindromic repeats (CRISPR). Objectives: The goal of this study was to explore the diversity of C. jejuni isolates with CRISPR from an animal farm. Methods: Seventy‐seven C. jejuni isolates from an animal farm were used in this study. The day‐old broilers were reared with other poultry and farm animals, including layer hens, guinea hens, dairy goats and sheep. A small swine herd was also present on an adjacent, but separate plot of land. Isolation and identification of C. jejuni were performed according to the standard procedures. The CRISPR type 1 was PCR amplified from genomic DNA, and the amplicons were sequenced by the Sanger dideoxy method. The direct repeats (DRs) and spacers of the CRISPR sequences were identified using the CRISPRFinder. Results: The CRISPR sequences were detected in all 77 isolates. One type of DRs was identified in these 77 isolates. The lengths of the CRISPR locus ranged from 100 to 560 nucleotides, whereas the number of spacers ranged from one to eight. The distributions of the numbers of CRISPR spacers from different sources seemed to be random. Overall, 17 out of 77 (22%) C. jejuni isolates had two and five spacers, whereas 14 out of 77 (18%) isolates had three spaces in their genomes. By further analysis of spacer sequences, a total of 266 spacer sequences were identified in 77 C. jejuni isolates. By comparison with known published spacer sequences, we observed that 49 sequences were unique in this study. The CRISPR sequence combination of Nos. 16, 19, 48 and 57 was found among a total of 15 C. jejuni isolates containing various multi‐locus sequence typing (MLST) types (ST‐50, ST‐607, ST‐2231 and ST‐5602). No. 57 spacer sequence was unique from this study, whereas the other three (Nos. 16, 19 and 48) sequences were found in previous reports. Combination of Nos. 5, 9, 15, 30 and 45 was associated with ST‐353. To compare the CRISPR genotyping with other methods, the MLST was selected due to its high discriminatory power to differentiate isolates. Based on calculation of the Simpson's index of diversity, a combination of both methods had higher Simpson's index value than those for CRISPR or MLST, respectively. Conclusions: Our results suggest that the MLST from C. jejuni isolates can be discriminated based on the CRISPR unique spacer sequences and the numbers of spacers. In the future, investigation on the CRISPR resolution for C. jejuni identification in outbreaks is needed. A database that integrates both MLST sequences and CRISPR sequences and is searchable is greatly in demand for tracking outbreaks and evolution of this bacterium. Abstract : Fig. 1 Distribution of the numbers of CRISPR spacers in Campylobacter jejuni isolates from an animal farm in 2016. The x‐axis indicates the numbers of CRISPR spacers. The y‐axis represents the numbers of Campylobacter jejuni isolates.